Suboptimal glycemic control in adolescents and young adults with type 1 diabetes from 2011 to 2020 across Australia and New Zealand: Data from the Australasian Diabetes Data Network registry. Issue 6 (10th June 2022) - James, Steven; Perry, Lin; Lowe, Julia; Harris, Margaret; Craig, Maria E.; ,
Abstract: Background: Competing challenges in adolescence and young adulthood can distract from optimal type 1 diabetes (T1D) self‐management, and increase risks of premature morbidity and mortality. There are limited data mapping the glycemic control of people with T1D in this age group, across Australasia. Research Design and Methods: Clinical data were extracted from the Australasian Diabetes Data Network, a prospective clinical diabetes registry. Inclusion criteria were individuals with T1D aged 16–25 years at their last recorded T1D healthcare visit (from 1st January 2011 to 31st December 2020), with T1D duration of at least 1 year. Data were stratified by two last recorded T1D healthcare visit ranges, while generalized estimated equation (GEE) modeling was used to examine factors associated with HbA1c across visits during the 10 year period. Results: Data from 6329 young people (52.6% male) attending 24 diabetes centers across Australasia were included. At the last visit within the most recent 5 years, mean ± SD age was 18.5 ± 2.3 years, T1D duration was 8.8 ± 4.7 years and HbA1c was 8.8 ± 1.8% (72.2 ± 19.9 mmol/mol); only 12.3% had an HbA1c below the international target of <7.0% (53 mmol/mol). Across all T1D healthcare visits, in GEE modeling, higher HbA1c was associated with female sex ( B = 0.20; 95% CI 0.12 to 0.29, p < 0.001), longer T1D duration ( B = 0.04, 0.03 to 0.05, p < 0.001). Lower HbA1c was associated with attendance at a pediatric T1D healthcare setting ( B = −0.33, −0.45 to −0.21, p < 0.001) and use of CSII versus BD/MDI therapy ( B = −0.49, −0.59 to 0.40, p < 0.001). Conclusions: This Australasian study demonstrates widespread and persistent sub‐optimal glycemic control in young people with T1D, highlighting the urgent need to better understand how healthcare services can support improved glycemic control in this population.